2016
DOI: 10.1002/ajpa.22990
|View full text |Cite
|
Sign up to set email alerts
|

A validated method for modeling anthropoid hip abduction in silico

Abstract: Our models broadly correspond to in vivo data on hip abduction, although the relationship between the models and live animal data is less straightforward than hypothesized. The models can predict acrobatic or stereotyped locomotor adaptation for taxa with values near the extremes of the range of abduction ability. Our findings underscore the difficulties associated with modeling complex systems and the importance of validating in silico models. They suggest that models of joint mobility can offer additional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 102 publications
(182 reference statements)
1
30
1
Order By: Relevance
“…Simulations based on long-tailed ( M. fascicularis ) and pig-tailed ( M. nemestrina ) macaques predicted that hip abduction should be about 47° (range of 39–57°) (Hammond et al, 2016), which is significantly higher than that observed in captive rhesus (mean 25°, range 10–37°) and long-tailed macaques (mean 26°, range 20–36°) (Hammond, 2014a). The range of abduction (i.e., 20–62°) in the free-ranging rhesus macaques measured here overlaps with the simulation data, suggesting that the Hammond et al (2016) model of hip abduction predicts joint excursions in Macaca better than previously realized. This study highlights the discrepancy between measures of hip abduction in captive and free-ranging rhesus macaques and underscores the need for caution when selecting in vivo samples for locomotor studies, as small cage-confinement can impact joint mobility in monkeys.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Simulations based on long-tailed ( M. fascicularis ) and pig-tailed ( M. nemestrina ) macaques predicted that hip abduction should be about 47° (range of 39–57°) (Hammond et al, 2016), which is significantly higher than that observed in captive rhesus (mean 25°, range 10–37°) and long-tailed macaques (mean 26°, range 20–36°) (Hammond, 2014a). The range of abduction (i.e., 20–62°) in the free-ranging rhesus macaques measured here overlaps with the simulation data, suggesting that the Hammond et al (2016) model of hip abduction predicts joint excursions in Macaca better than previously realized. This study highlights the discrepancy between measures of hip abduction in captive and free-ranging rhesus macaques and underscores the need for caution when selecting in vivo samples for locomotor studies, as small cage-confinement can impact joint mobility in monkeys.…”
Section: Discussionmentioning
confidence: 90%
“…A larger span at the knee should reflect a greater hindlimb envelope (i.e., a greater reach of the hindlimb), allowing an animal to reach further for more distantly placed arboreal supports (see also Hammond, 2014a; b; Hammond et al, 2016; Preuschoft et al, 2016). Because an increased limb envelope increases arboreal competency, and is also increased by higher levels of abduction, this suggests to us that the observed increase in hip abduction in free-ranging animals is likely to be biologically meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3-D Dromaius meshes were scaled to the same proportional size as the Australovenator bone meshes. This provided a guide to digitally articulate the Australovenator bones in the same weight-bearing position as the Dromaius specimen which enabled an ‘ in silico’ (Hammond, Plavcan & Ward, 2016) restoration of the Australovenator pes considering both soft tissue attachment points and proportions (See Fig. 11 in White et al, 2016).…”
Section: Methodsmentioning
confidence: 99%